Stomach Disorders - Chai, Jianyuan (IntechOpen, 2018)
We have realized that this is a rather light book by weight, but the subject is quite heavy. The stomach is not just a digestive organ. In fact, it carries many important duties far beyond digestion. No matter whether you are an educator, or a medical practitioner, or just a regular reader with a lot of curiosities, we hope after reading you will learn to appreciate this precious organ and take good care of it. Next time when you are eating, please think about what you are doing to your stomach.